Influx of Muslim traders in Iloilo City - Barba, Vera Mie; de la Mesa, Ashanti; Maraginot, Mutya; Mendez, Catherine Julia
Executive Summary - This study aims to develop an understanding of the future that brought the influx of Muslim traders in Iloilo City. There were 36 Muslim trader surveyed from different trading centers around the ciity. Data analysis employed content analysis, percentage analysis, mean mode, correlations and regression analysis. The independent variables in this study are the religion differences, economic condition of Iloilo City, local government policies of the city and the peace and order situation in Mindanao. Results reveal that religion differences of the Muslims and the Ilonggos did not have an effect in the influx of the former to the latter's place. While the economic condition, local government policies and the peace and order situation in Mindanao have a significant impact on the study of the influx of Muslim people.